Effect of Mercuric Chloride on Kinetic Properties of Horseradish Peroxidase - N Einollahi; S Abbasi; N Dashti; F Vaezzadeh (Tehran University of Medical Sciences, 2006)
Mercury is one of the three major environmental metal poisons, and mercuric chloride is a highly reactive compound which can harm cells by a variety of mechanisms including direct interaction with sulphydryl groups of proteins and enzymes, therefore affecting the enzymatic activity. This study focused on the effect of Hg++ on horseradish peroxidase (donor: hydrogen peroxide oxidoreductase, EC 1.11.1.7) (HRP) (Isoenzyme C) activity. In the presence of 88 mM hydrogen peroxide Km for o-dianisidine oxidation was 0.05 millimolar and Vmax was 8.5 M.s-1. Incubation of the enzyme with 1 to 100 millimolar mercuric chloride for 5-20- and 60 min resulted in progressive inhibition of the enzymatic activity. At low Hg++ concentrations the inhibition was reversible by excess substrate, while at high Hg++ concentration the inhibition was not reversible. Results also indicated that the type of inhibition depended on the duration of incubation of the enzyme with metal ion and on the Hg++ concentration. So we could conclude that the type of inhibition changed from noncompetitive to mix with increased incubation time and increased metal concentration.